El despido intempestivo en la ciudad de Machala, aplicación del código del trabajo - Alarcón Velásquez, Lissett Estefanía; Pérez Tirado, Diana Belén (Machala, 2019)
In order to characterize the application of the Labor Code in relation to untimely dismissal, a descriptive investigation with a quantitative-qualitative approach was carried out in the city of Machala in the first four months of 2018. The methodological strategy was systematized by scientific research methods: historical-logical, documentary review, analytical-synthetic, statistical and data triangulation. For the collection of information, a survey was applied to 120 randomly selected workers and an interview to 35 labor law specialists chosen intentionally. The results obtained reveal, in the context of the city of Machala, the existence of asymmetry between praxis and the doctrine that regulates the rules of untimely dismissal; there is a coincidence of criteria between specialists and workers, who participated in the study; mean that compensation for this concept is more an institution that seeks to persuade the employer of the application of untimely dismissal, that an economic compensation to the worker for the damages caused and for the years of delivery for the benefit of the employer, does not cover the needs of the employer. worker and his family to maintain a dignified and decent life until finding a new job.
Con el objetivo de caracterizar la aplicación del Código del Trabajo en lo relativo al despido intempestivo, se realizó en el primer cuatrimestre del año 2018 una investigación descriptiva con enfoque cuanti-cualitativo en la ciudad de Machala. La estrategia metodológica fue sistematizada mediante los métodos científicos de investigación: histórico-lógico, revisión documental, analítico-sintético, estadístico y triangulación de datos. Para la recolección de la información se aplicó una encuesta a 120 trabajadores seleccionados aleatoriamente y una entrevista a 35 especialistas del Derecho Laboral escogidos intencionalmente. Los resultados obtenidos develan, en el contexto de la ciudad de Machala, la existencia de asimetría entre la praxis y la doctrina que regula las normas del despido intempestivo; existe coincidencia de criterios entre los especialistas y trabajadores, que participaron en el estudio; significan que la indemnización por este concepto es más una institución que procura persuadir al empleador de la aplicación del despido intempestivo, que una compensación económica al trabajador por los perjuicios ocasionados y por los años de entrega en beneficio del empleador, esta no cubre las necesidades del trabajador y su familia para mantener una vida digna y decorosa hasta encontrar un nuevo empleo.
Keywords: CODIGO DEL TRABAJO; INDEMNIZACION; DESPIDO INTEMPESTIVO